2022
DOI: 10.3390/ma15249046
|View full text |Cite
|
Sign up to set email alerts
|

The Mutual Incorporation of Mg2+ and CO32− into Hydroxyapatite: A DFT Study

Abstract: Hydroxyapatite (HA) with a stoichiometry composition of Ca10(PO4)6(OH)2 is widely applied for various biomedical issues, first of all for bone defect substitution, as a catalyst, and as an adsorbent for soil and water purification. The incorporation of foreign ions changes the acid–base relation, microstructure, porosity, and other properties of the HA materials. Here, we report the results of calculations of the density functional theory and analyze the possibility of two foreign ions, CO32− and Mg2+, to be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 73 publications
2
9
0
Order By: Relevance
“…The O–H bond where the H atom is located between the oxygen atoms of the shortening O⋯O pair becomes as long as 0.992 Å (compared to 0.979 Å in unperturbed anion channel of pure HA), but the O–H linkage of the inclined to Li + hydroxyl group becomes as short as 0.977 Å. These features of the geometry adjustment are strikingly different from those in the presence of other cations, where the oxygen atom of hydroxyl shifts from the anion channel axis towards the cation to shorten the distance to the foreigner ion [ 19 , [28] , [29] , [30] ].…”
Section: Resultsmentioning
confidence: 99%
“…The O–H bond where the H atom is located between the oxygen atoms of the shortening O⋯O pair becomes as long as 0.992 Å (compared to 0.979 Å in unperturbed anion channel of pure HA), but the O–H linkage of the inclined to Li + hydroxyl group becomes as short as 0.977 Å. These features of the geometry adjustment are strikingly different from those in the presence of other cations, where the oxygen atom of hydroxyl shifts from the anion channel axis towards the cation to shorten the distance to the foreigner ion [ 19 , [28] , [29] , [30] ].…”
Section: Resultsmentioning
confidence: 99%
“…Another study by Laurencin et al reported the lattice distortion by Mg incorporation but mentioned falls in the lattice parameter (a) due to the substitution [88]. Further, Mg 2+ can substitute Ca (1) or Ca (2) sites and lead to a shortening distance between Mg and O [89]. In addition, Goldberg et al prepared Mg-HAP and reported that the substituting using Mg 2+ ions led to an increase in BET-specific surface area from 23.35 to 86.91 m 2 /g from 0 to 1% substitution.…”
Section: Magnesium (Mg 2+ )mentioning
confidence: 99%
“…They do not fully dissolve in water but are slightly soluble at high pH levels (1.71 = mg L −1 at pH = 6.69) [ 136 ]. The ionic radius of Mg ++ is 72 pm [ 137 ]. They can disrupt cellular activity and release ROS.…”
Section: Antimicrobial Polymersmentioning
confidence: 99%
“…They are sparingly soluble in water and able to form colloidal suspensions. The ionic radius of Mg ++ is 72 pm [ 137 ]. The mode of action involves activating ROS [ 141 ].…”
Section: Antimicrobial Polymersmentioning
confidence: 99%